Crowley's an introduction to human disease : pathology and pathophysiology correlations - Reisner, Emily G.; Reisner, Howard M. (Burlington, MA : Jones & Bartlett Learning, 2022)
Updated to keep pace with the many changes in the field, Crowley's An Introduction to Human Disease: Pathology and Pathophysiology Correlations, Eleventh Edition provides readers with a clear, well-illustrated explanation of the structural and functional changes associated with disease, the clinical manifestations of disease, and how to determine treatment. It reflects current information on the pathenogenesis of infectious disease and how changes in the genome are expressed as disease. The first chapters of the text discuss general concepts and diseases affecting the body as a whole. Later chapters consider the various organ systems and their diseases. The Eleventh Edition includes new content on COVID-19, Zika virus, brain eating amoebas, plus mini podcasts to address difficult concepts such as cancer and the use of microscope slides.
General concepts of disease: principles of diagnosis -- Cells and tissues: their structure and function in health and disease -- Genes, DNA, chromosomes, and cell division -- Congenital and hereditary diseases -- Inflammation and repair -- Immunity, hypersensitivity, allergy, and autoimmune diseases -- Neoplastic disease -- Pathogenic microorganisms -- Parasitic disease -- Communicable disease control and sexually transmitted disease -- The cardiovascular system -- Diseases of blood circulation -- The hematopoietic and lymphatic systems -- Abnormalities of blood coagulation -- The respiratory system -- The breast -- The female reproductive system -- Prenatal development and conditions associated with pregnancy -- The urinary system and fluid homeostasis -- The male reproductive system -- The liver and the biliary system -- The pancreas and diabetes mellitus -- The gastrointestinal tract -- The endocrine glands -- The nervous system -- The musculoskeletal system.
Includes bibliographical references and index.
Online resource; title from electronic title page (ProQuest Ebook Central, viewed on December 1, 2020).
WorldCat record variable field(s) change: 650
Keywords: Physiology, Pathological; Pathology; Diseases; Disease; Pathology; Physiopathologie; Pathologie; Maladies; pathology; Pathology; Physiology, Pathological; Electronic books